KESIAPAN GPAI SMP DALAM IMPLEMENTASI KTSP PAI - Neni Setianingsih (Badan Litbang dan Diklat Kementerian Agama RI, 2008)
AbstractThe validation of Education Unit Level Curriculum/ Kurikulum Tingkat Satuan Pendidikan (KTSP) is one of some realization of autonomy implementation. The implementation of KTSP including the KTSP of Islamic religion education tends to be minimally implemented. Some of its indicators are, in fact, a great deal of the teachers of Islamic religion/ Guru Pendidikan Agama Islam (GPAI) have not been applied, developed, or implemented such curriculum in the because of some factor dealing with their level of preparation of GPAI SMP in implementing of KTSP PAI and also supporting and obstacle factors in the implementation in schools.